Child Custody Rights After Divorce in Indonesia from a Contemporary Islamic Family Law Perspective - Mustafid Mustafid; Khairunnas Rajab; Arisman Arisman; Muhammad Faiz Algifari (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The research explores the issue of child custody (hadhanah) in Indonesia after divorce, focusing on the challenges arising from the increasing divorce rates. It addresses the gap between classical Islamic jurisprudence, which traditionally prioritizes maternal rights, and the modern social realities that necessitate multidimensional considerations—legal, psychological, and social. The novelty of this study lies in its attempt to reconstruct the concept of child custody by harmonizing the principles of Islamic family law with the evolving needs of modern Indonesian society. This is achieved through the reinterpretation of classical fiqh texts using contemporary approaches, such as maslahah mursalah (public interest) and maqasid al-shariah (objectives of Islamic law), to align them with the principle of the best interest of the child. The research employs a qualitative methodology with a normative-sociological approach, supported by a literature review. Primary data is derived from classical Islamic jurisprudence literature and contemporary Islamic legal thought, while secondary data includes Indonesian legislation such as the Compilation of Islamic Law and the Marriage Law, alongside relevant scholarly articles. The findings reveal the urgent need to reinterpret the concept of hadhanah in a way that reflects current social, legal, and psychological considerations. The research emphasizes that harmonizing traditional sharia norms with modern social realities will enable the application of more humanistic Islamic law, thus contributing to the development of a contextual and equitable framework for Islamic family law in Indonesia. This approach helps address contemporary challenges and strengthens the adaptability of Islamic family law in the modern era.